2021
DOI: 10.3390/toxins13050332
|View full text |Cite
|
Sign up to set email alerts
|

Botulinum Toxin Type-A (Botulax®) Treatment in Patients with Intractable Chronic Occipital Neuralgia: A Pilot Study

Abstract: Intractable chronic occipital neuralgia (ON) is an uncommon type of headache often experienced by patients in outpatient neurological clinics. Among patients unresponsive to oral neuralgia medications, needling or injections with several drugs were suggested alternatives for treating chronic ON. This study aimed to determine the effectiveness and safety of botulinum toxin type-A (BTX-A) injection treatments, where eight patients with unilateral chronic ON received BTX-A injections at the pain sites. The pain r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…The participants received injections of BTX-A at the sites of pain. The study confirmed our hypothesis by demonstrating that BTX-A was both safe and effective in the treatment of ON [6].…”
Section: Btx-a As a Treatment Optionsupporting
confidence: 85%
See 2 more Smart Citations
“…The participants received injections of BTX-A at the sites of pain. The study confirmed our hypothesis by demonstrating that BTX-A was both safe and effective in the treatment of ON [6].…”
Section: Btx-a As a Treatment Optionsupporting
confidence: 85%
“…Kim et al [6] Despite the research being conducted by a small group, the results are significant and can make a difference in the medical field. This study is one of the few medical studies that evaluate the use of BTX-A for the treatment of chronic ON.…”
Section: Yan Et Al [4]mentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 823 unique studies were identified, of which 19 studies (between 2005 and 2021) fulfilled the inclusion criteria and were included in this systematic review and meta-analysis. [11,12,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] Fifteen studies included 916 subjects with neuralgia at the start of the study; 462 of them were using acupuncture and 454 were given other medication as control. Four studies discussed the safety parameter for acupuncture compared with control including 159 for acupuncture group and 158 for control group.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, most of these studies were carried out in Asian countries and not widely applied in other cultures which may bias the findings of the current studies by reporting a lower degree of pain following acupuncture (placebo effect). Acupuncture plus medication had a significantly higher effective rate of treatment compared to medication in the treatment of occipital neuralgia.. [11,12,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] Four studies used for analysis for acupuncture safety, the acupuncture group showed a significantly (P = .003) lower number of adverse events compared with control group (medication) which reflect the suitability of acupuncture compared with tradition medications.…”
Section: Discussionmentioning
confidence: 99%